Exploring the Primary Models and Their Efficacy of Health Education in Universities in the Zhanjiang Area During the Post-COVID-19 Era - he, junchu; jiang, zhuofei; Yang, Yanyan; yuan, Jiacheng; Daniel Wong, Barrenechea (Pacific International Journal, 2025)
Objective Exploring the main models and educational effects of health education in undergraduate institutions in the post pandemic era in Zhanjiang region. Methods Randomly select second year students from two universities in Zhanjiang area to conduct a survey on health education models, and collect 2000 valid questionnaires; Randomly select 600 research subjects, divide them into three groups, and carry out training on three health education modes. Statistical analysis will be conducted on the awareness of infectious diseases (taking syphilis as an example) before and after the training.Results The three most popular models are "WeChat official account push", "set up stalls to distribute publicity materials" and "popular science lectures on infectious disease prevention and control". There was no statistically significant difference (P>0.05) in the number of syphilis awareness among colleges and gender groups. Prior to training, statistical knowledge was obtained, and there was no statistically significant difference (P>0.05), indicating that the three groups had the same level of knowledge; There were statistically significant differences (P<0.05) between the pre - and post training groups, indicating that all three educational models were effective. After training, there was a statistically significant difference between the groups (P<0.05), indicating that the three educational models had inconsistent effects; Compared with the other two groups, the "WeChat official account push" group had a statistically significant difference (P<0.05), indicating that the "WeChat official account push" model had the best effect; Compared with the other two groups, there was no statistically significant difference (P>0.05), indicating that the educational effects of the two modes were comparable.Conclusion In the post epidemic era in Zhanjiang, the most popular health education models include WeChat official account push, setting up booths to distribute publicity materials and popular science lectures on infectious disease prevention and control; The educational effect of WeChat official account push is the best, which is worth promoting vigorously; At the same time, we should also leverage the other two models to continuously carry out health education for college students and improve their level of infectious disease prevention and control.